2024
DOI: 10.3389/froh.2024.1360340
|View full text |Cite
|
Sign up to set email alerts
|

Fungal footprints in oral cancer: unveiling the oral mycobiome

Jessica Sonal Monteiro,
Kriti Kaushik,
José Alcides Almeida de Arruda
et al.

Abstract: Oral squamous cell carcinoma (OSCC) is the most common type of head and neck cancer, with a high mortality rate. There is growing evidence supporting a link between oral cancer and the microbiome. The microbiome can impact various aspects of cancer, such as pathogenesis, diagnosis, treatment, and prognosis. While there is existing information on bacteria and its connection to oral cancer, the fungi residing in the oral cavity represent a significant component of the microbiome that remains in its early stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 115 publications
(126 reference statements)
0
0
0
Order By: Relevance
“…Whereas species like Streptococcus salivarius subsp. salivarius, Scapharcabroughtonii, Mortierellaechinula, and Morchella septimelata were diminished [86].…”
Section: Oral Potentially Malignant Disorders Oral Cancer and Oral My...mentioning
confidence: 96%
See 1 more Smart Citation
“…Whereas species like Streptococcus salivarius subsp. salivarius, Scapharcabroughtonii, Mortierellaechinula, and Morchella septimelata were diminished [86].…”
Section: Oral Potentially Malignant Disorders Oral Cancer and Oral My...mentioning
confidence: 96%
“…Heng et al suggested a group of signature species composed of bacteria and fungi, which are closely associated with the sequence health-premalignancy-carcinoma in oral squamous cell carcinoma [86]. The identified signature species were Prevotella intermedia, Porphyromonas endodontalis, Acremonium exuviarum, and Aspergillus fumigatus, which prospered in oral carcinoma [86]. Whereas species like Streptococcus salivarius subsp.…”
Section: Oral Potentially Malignant Disorders Oral Cancer and Oral My...mentioning
confidence: 99%